COVID-19 vaccination and test management for healthcare workers—development, implementation and feasibility of a custom human resources information platform at a university hospital - Matthias Bonigut; Ana Zhelyazkova; Mathias Weber; Stefanie Geiser-Metz; Markus Geis; Bernhard Heindl; Stephan Prückner (BMC Medical Informatics and Decision Making)
Abstract Background The continuously evolving legislative and reporting requirements during the COVID-19 pandemic posed the demand for establishing an efficient real-time human resources management system at the LMU University Hospital, one of the largest university hospitals in Germany. Developing a system allowing for agile real-time analysis as well as for reporting employees’ COVID-19 vaccination and testing status while ensuring the security of personnel data presented several technical and managerial challenges. Methods We designed and implemented a custom COVID-19 human resources information platform in order to fulfill the LMU University Hospital’s legal requirement to report employees’ vaccination and testing status. We designed the platform as an all-in-one solution for all relevant COVID-19 data, merged from five individual sources. The development process was guided by the principles of findability, accessibility, interoperability and reusability (FAIR) with particular focus on interoperability. Here, we present the platform’s design, cumulative user data and discuss the feasibility of the approach including its intended and unintended outcomes. Results The COVID-19 human resources management platform was the first solution of its kind at the LMU University Hospital, emerging from the specific need for an efficient exterior and interior mandate fulfillment. It served both for operational management purposes as well as for strategic pandemic and hospital management. The immediate dependency on data privacy and regulatory adaptations due to the evolving pandemic situation posed the necessity for regular adaptations to the platform’s structure. Conclusions The presented case reveals how data utilization requires the concurrent and proactive consideration of data security and interoperability against the background of a scalable architecture. Simultaneously, the development of such platforms needs to be open to new cases, functions and sources, thus requiring a dynamic and agile environment.